Care needs and economic consequences after acute ischemic stroke: The Erlangen Stroke Project - Ward, Alexandra; Payne, K. A.; Caro, J. J.; Heuschmann, P. U.; Kolominsky-Rabas, Peter (European Journal of Neurology, 2005)
The objective was to determine the functional outcome, location of care and economic consequences in the first 3 months after ischemic stroke. As part of the Erlangen Stroke Project. (ESPro) information was collected on patients suffering a first-ever ischemic stroke. Three months after the stroke, location of care, dependence on caregivers and function based on Barthel Index: poor (0-55). moderate (60/\90) or good function (95-100) were recorded. Data about health services used were combined with cost estimates for Germany (2000 Euros, undiscounted). Of 491 patients hospitalized, 383 were alive 3 months afterwards, 79% residing in the community. The majority of patients with poor function (60%) were still in institutional care. Patients with good function typically accrued the lowest costs, whether in an institution (17 965) or not (11 032) compared with poorer function who were living in an institution (poor: 26 370; moderate: 28,121), or community (poor: 27,207; moderate: 19,350). Hospitalization and rehabilitation services were the major costs accrued at each level of function. Many patients were left requiring a substantial amount of care and the costs associated with providing institutional care has a major impact on the economic consequences of a stroke. © 2005 EFNS.
Created from Fastlane, Scopus look-up
Keywords: Acute ischemic stroke; Care needs; Costs; Erlangen Stroke Project; Germany